(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2015)
A low-gradeantimony deposit originating from district Qilla Abdullah, Balochistan Province of Pakistan, containing stibnite as an economical mineral was beneficiated by froth flotation technique. Flotation parameters such as particle size of the feed, pulp density, pH of the pulp, agitation speed, type and dose of reagents (i.e. collector, frother, activator, regulator and modifier) and the conditioning time were studied on the basis of single-factor variation experiment in order to get the optimum grade and recovery. Regrinding of the rougher concentrate followed by cleaning andrecleaning of rougher concentrateensured a final concentrate grade of 65.12% Sb@ 85.79% recovery. This concentrate is suitable for the extraction of metal and production of chemicals. DOI: http://dx.doi.org/10.3329/bjsir.v49i2.22003 Bangladesh J. Sci. Ind. Res. 49(2), 95-102, 2014